The heart's journey - Cameron, Barbara, 1949- (Cameron, Barbara, 1949- Stitches in time series., 2012)
"Naomi knows she should be excited about her upcoming wedding but she remains unmoved. Not only are her feelings for her fiance lackluster but she believes he may see her more as a servant than a partner. And he's so controlling. Is it too late to back out of the marriage?"--Provided by publisher.